Mindful-Based Cognitive Therapy Approach Bibliotherapy Techniques in Increasing Self Confidence in Cyberbullying Victims - Nasution, Salsabila; Firman, Firman; Netrawati, Netrawati (Universitas Trunojoyo Madura, 2023)
In the millennial era, the development of technology, information and communication is moving very rapidly. especially in the field of communication which is one of the most frequently used technologies today. Technology has both positive and negative impacts. One of the positive impacts is the ease of interacting with other people, but the negative impact of technology that most often occurs is verbal insults carried out on social media and is called cyberbullying. One of the problems that arise from cyberbullying is self-confidence. Counseling is analyzed to increase self-confidence for cyberbullying victims supported by a mindful-based cognitive therapy approach that will help participants learn how to recognize their feelings and see themselves as separate from their thoughts and moods. Supported by bibliotherapy techniques that focus on healing because it is believed that readers can influence individual attitudes, feelings, and behavior as expected.